Hubungan Kebiasaan Membaca Menggunakan Gawai dalam Posisi Berbaring dengan Kelainan Refraksi Mata (Miopia) pada Siswa Kelas VIII di SMPN 119 Kelurahan Cempaka Baru Jakarta Pusat: Pemeriksaan Menggunakan Snellen Chart dan Tinjauannya menurut Pandangan Islam - Fenie Oktafiani Budi; Diniwati Mukhtar (Pusat riset dan Inovasi Nasional, 2026)
The increasing use of digital devices among adolescents raises concerns regarding eye health, particularly myopia. Non-ergonomic postures, such as using gadgets in a lying position, may increase accommodative stress on the eyes and contribute to visual impairment. To analyze the association between the duration and viewing distance of gadget use in a lying position and the occurrence of myopia among eighth-grade students at SMPN 119 Central Jakarta. An observational analytic study with a cross-sectional design was conducted involving 74 eighth-grade students. Data on gadget use habits, including duration and viewing distance, were collected using a structured questionnaire. Visual acuity was assessed using a Snellen chart. Bivariate analysis was performed using the Chi-square test with a significance level of p < 0.05. Decreased visual acuity was found in 62.2% of respondents. There was no significant association between viewing distance and myopia (p = 0.080). However, a significant association was identified between gadget use duration exceeding two hours per day and the occurrence of myopia (p = 0.002). The duration of gadget use in a lying position was significantly associated with myopia, whereas viewing distance was not. Limiting the duration of gadget use may help prevent visual impairment among adolescents.